Comparative anatomy of nitrergic intrinsic choroidal neurons (ICN) in various avian species - Schrödl, Falk; De Stefano, M. Egle; Reese, Sven; Brehmer, Axel; Neuhuber, Winfried (Experimental Eye Research, 2004)
Intrinsic choroidal neurons (ICN) represent a peculiar feature of eyes in higher primates and birds. They account for up to 2000 in human and duck eyes but are virtually absent or rare in all other mammalian species investigated so far. It has been suggested that ICN are involved in regulation of ocular blood supply, hence influencing intraocular pressure, and changes in choroidal thickness, thus influencing accommodation. The present study was undertaken in order to compare differences in various avian species with respect to ICN as well as to provide data on some avian species relevant for experimental ophthalmic research, i.e. chicken and quail. Choroids from 12 avian species were processed for NADPH-diaphorase histochemistry or, in some cases, neuronal nitric oxide synthase immunocytochemistry. ICN were quantified and normalized to mean choroidal area. Three choroids of each galliformes (i.e. chicken, quail, turkey) and anseriformes (i.e. Muscovy duck, Mallard duck, goose) were rastered in squares of 1 mm and x/y coordinates were transferred into a 3D-diagram with the amount of ICN represented in the z-axis. ICN were detected in all species investigated. They were predominantly small cells with soma diameters of 20-30 μm. In turkey, and to a lesser amount in chicken, a subpopulation of ICN with somal diameters of up to 70 μm was observed. Highest mean cell counts were found in goose (6195.4; turkey 3558.4; chicken 1681.4; Muscovy duck 785.4; Mallard duck 640.8; quail 440.2). Normalized to choroidal area, highest mean cell counts were (per mm): 12.62 in goose, 4.42 in both chicken and turkey, 2.86 in quail, 2.66 in Mallard duck and 1.89 in Muscovy duck. In galliformes, ICN were found to be accumulated temporo-cranial, while in anseriformes they were arranged in a more belt-like fashion, passing from cranio-nasal to temporo-caudal. Our results show that besides Muscovy duck, other avian species appear as suitable models for further functional experiments on ICN. The temporo-cranial accumulation of ICN in galliformes and the belt-like arrangement in anseriformes may reflect special functional requirements in regions of high visual acuity. © 2003 Elsevier Ltd. All rights reserved.
Keywords: Accommodation; Eye; Neuronal nitric oxide synthase; Non-vascular smooth muscle; Vascular innervation; VIP